PROBLEMS OF PROVIDING AND LEGALITY OF EVIDENCE IN THE CRIMINAL ACTS OF TRAFFICKING NARCOTICS CLASS I NON-PLANT BASED ON LAW NUMBER 35 OF 2009 - Aswin Suwardi; Appe Hutauruk; Hotman Sinambela; Fendi Maruba Parlindungan Hutahaean (JILPR Journal Indonesia Law and Policy Review, 2026)
The crime of trafficking in Class I narcotics, not plants, is an extraordinary crime and poses significant obstacles for law enforcement officials in the criminal evidence process. This study aims to examine and analyze the evidentiary process and the legality of evidence in this crime, as well as to identify strategies to improve investigators’ skills in collecting and analyzing evidence to address the dynamics of illicit drug trafficking networks. The research method used is a normative method with a legislative and conceptual approach. The legal sources used include primary legal materials in the form of narcotics-related legislation and criminal procedure law, as well as secondary legal materials in the form of scientific literature and books. The data obtained were analyzed descriptively and qualitatively to produce systematic conclusions. The results show that the evidentiary system for trafficking in Class I narcotics, not plants, combines the general provisions of the Criminal Procedure Code (the negative wettelijk principle) with the special provisions (lex specialis) of Law Number 35 of 2009. This regulation broadens the scope of evidence by recognizing electronic information and documents as valid indicative evidence. In addition, to overcome the dynamic modus operandi, investigators’ skills must be improved through mastery of digital forensics, strengthening cross-institutional cooperation (National Police, National Narcotics Agency, Prosecutor’s Office, Forensic Laboratory), and optimizing special investigative techniques such as wiretapping, undercover buying, and controlled delivery so that the fulfillment of a minimum of two valid pieces of evidence that guarantee legal certainty, justice, and the protection of human rights can be realized.